(untitled) (Journal of Applied Oral Science, 2015)
Objective This study investigated the marginal and internal adaptation of individual dental crowns fabricated using a CAD/CAM system (Sirona’s BlueCam), also evaluating the effect of the software version used, and the specific parameter settings in the adaptation of crowns.Material and Methods Forty digital impressions of a master model previously prepared were acquired using an intraoral scanner and divided into four groups based on the software version and on the spacer settings used. The versions 3.8 and 4.2 of the software were used, and the spacer parameter was set at either 40 μm or 80 μm. The marginal and internal fit of the crowns were measured using the replica technique, which uses a low viscosity silicone material that simulates the thickness of the cement layer. The data were analyzed using a Friedman two-way analysis of variance (ANOVA) and paired t-tests with significance level set at p